The effect of symmetric and asymmetric information on volatility structure of crypto-currency markets: a case study of bitcoin currency - Othman, Anwar Hasan Abdullah; Syed Jaafar Alhabshi, Syed Musa; Haron, Razali (Emerald Publisher, 2019)
Purpose – This paper aims to examine whether the crypto-currencies’ market returns are symmetric or asymmetric informative, through analysing the daily logarithmic returns of bitcoin currency over the period of 2011-2017.